With-No-Lysine Kinase 4 Mediates Alveolar Fluid Regulation in Hyperoxia-Induced Lung Injury*. Issue 10 (October 2015) - Lin, Hsueh-Ju; Wu, Chin-Pyng; Peng, Chung-Kan; Lin, Shih-Hua; Uchida, Shinich; Yang, Sung-Sen; Huang, Kun-Lun
Abstract : Objectives: To investigate mechanisms involved in the regulation of epithelial ion channels and alveolar fluid clearance in hyperoxia-induced lung injury. Design: Laboratory animal experiments. Setting: Animal care facility procedure room in a medical center. Subjects: Wild-type, STE20/SPS1-related proline/alanine-rich kinase knockout (SPAK –/– ), and with-no-lysine kinase 4 knockin ( WNK4 D561A/+ ) mice. Interventions: Mice were exposed to room air or 95% hyperoxia for 60 hours. Measurements and Main Results: Exposure to hyperoxia for 60 hours increased the lung expression of with-no-lysine kinase 4 and led to STE20/SPS1-related proline/alanine-rich kinase and sodium-potassium-chloride cotransporter phosphorylation, which resulted in the suppression of alveolar fluid clearance and increase of lung edema. WNK4 D561A/+ mice at the baseline presented an abundance of epithelium sodium channel and high levels of STE20/SPS1-related proline/alanine-rich kinase and sodium-potassium-chloride cotransporter phosphorylation. Compared with the wild-type group, hyperoxia caused greater epithelium sodium channel expression in WNK4 D561A/+ mice, but no significant difference in STE20/SPS1-related proline/alanine-rich kinase and sodium-potassium-chloride cotransporter phosphorylation. The functional inactivation of sodium-potassium-chloride cotransporter by gene knockout in SPAK –/– mice yielded a lower severity of lung injury and longer animal survival, whereas constitutive expression of with-no-lysine kinase 4 exacerbated the hyperoxia-induced lung injury. Pharmacologic inhibition of sodium-potassium-chloride cotransporter by inhaled furosemide improved animal survival in WNK4 D561A/+ mice. By contrast, inhibition of epithelium sodium channel exacerbated the hyperoxia-induced lung injury and animal death. Conclusions: With-no-lysine kinase 4 plays a crucial role in the regulation of epithelial ion channels and alveolar fluid clearance, mainly via phosphorylation and activation of STE20/SPS1-related proline/alanine-rich kinase and sodium-potassium-chloride cotransporter. Abstract : Supplemental Digital Content is available in the text.